Micellar Form of a Ferrocene-Containing Camphor Sulfonamide with Improved Aqueous Solubility and Tumor Curing Potential - Maria Schröder; Maria Petrova; Georgi M. Dobrikov; Georgy Grancharov; Denitsa Momekova; Petar D. Petrov; Iva Ugrinova (MDPI AG, 2023)
The discovery of new anticancer drugs with а higher, more specific activity and diminished side effects than the conventional chemotherapeutic agents is a tremendous challenge to contemporary medical research and development. To achieve a pronounced efficacy, the design of antitumor agents can combine various biologically active subunits in one molecule, which can affect different regulatory pathways in cancer cells. We recently demonstrated that a newly synthesized organometallic compound, a ferrocene-containing camphor sulfonamide (DK164), possesses promising antiproliferative activity against breast and lung cancer cells. However, it still encounters the problem of solubility in biological fluids. In this work, we describe a novel micellar form of DK164 with significantly improved solubility in aqueous medium. DK164 was embedded in biodegradable micelles based on a poly(ethylene oxide)-b-poly(α-cinnamyl-ε-caprolactone-co-ε-caprolactone)-b-poly(ethylene oxide) triblock copolymer (PEO113-b-P(CyCL3-co-CL46)-b-PEO113), and the physicochemical parameters (size, size distribution, zeta potential, encapsulation efficiency) and biological activity of the obtained system were studied. We used cytotoxicity assays and flow cytometry to determine the type of cell death, as well as immunocytochemistry to assess the influence of the encapsulated drug on the dynamics of cellular key proteins (p53 and NFkB) and the process of autophagy. According to our results, the micellar form of the organometallic ferrocene derivate (DK164-NP) exhibited several advantages compared to the free substance, such as higher metabolic stability, better cellular uptake, improved bioavailability, and long-term activity, maintaining nearly the same biological activity and anticancer properties of the drug.